Prinsip Manajemen Tenaga Kependidikan Perspektif Al-Qur’an - Efi Tri Astuti (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2019)
As an effort to improve the quality of human resources, the development of human resources was important for the goverment to focus on improving the quality of education by provision learning processes with quality education personnel. This article aimed to discussed the principle management of educational staff of the Al-Qur'an perspective. This research was literature studies, namely by examining journals, books, research reports. The result showed that : (1) the Principle of Tawheed, covering the principle of unity of direction and unity of command; (2) Principles of justice and prosperity; (3) The principle of deliberation; (4) Principles of efficiency, effectiveness and productivity; (5) Disilpin principle, integrity and loyalty; (6) The principle of division of authority and responsibility; (7) Principle of Ukhuwah. An understanding of the management principle of the Al-Qur'an perspective in the management of Islamic education institutions will be able to contribute positively, including planning of education personnel, the process of recruitment, selection and placement, and the development of education personnel. Key words: Principle of Management, Educational Personnel, Al-Qur’an Perspektive